Use of a New Transportation Algorithm for Profit Maximization - Arifuzzaman, Arifuzzaman; Kader, Md. Salehin Ferdous; Alam, Homayra (European Scientific Journal, ESJ, 2019)
A transportation calculation is advanced, and it makes it possible to be able to effectively plan the assets with the end goal of augmenting the benefit of an assembling organization. The distribution indicators (DI) have been resolved from the distinction of the bigger unit profit and the average value of total unit profit of each row and column. Also, the area of the fundamental cells has been resolved as the biggest entrance of the transportation table (TT) along the biggest DI. The most extreme benefit given by this calculation is closer to the other benefit. The strategy, however, is represented with numerical examples to legitimize its proficiency.